Agroecological Homestead Model (AHM): technical and implementation report, Madhya Pradesh, India - Malaiappan, Sudharsan; Gadewar, P.; Goverdhanam, S.; Konwar, D.; Kumar, Gopal; Krishnan, S.; Sikka, Alok (International Water Management Institute, 2024)
The Agroecological Homestead Model (AHM), conceptualized under the CGIAR Agroecology Initiative in collaboration with PRADAN, provides an innovative framework to address critical challenges faced by tribal communities in Mandla district, Madhya Pradesh, India. These challenges include dietary monotony, malnutrition, irregular income, and resource degradation. Rooted in agroecological principles, AHM offers a sustainable and holistic approach to managing homestead resources.